ANALISIS KUALITAS WEB ZENIUS MENGGUNAKAN SYSTEM USABILITY SCALE (SUS) - Rasmila; Damsi, Ario; Jenni Cariyati Simanungklait; Apriliansyah, Rendi (CV. Hawari, 2022)
During the Covid-19 pandemic, many students found it difficult to carry out their studies, so many companies provided online learning services to make it easier for students to learn. One of them is PT Zenius Education which provides online learning services, PT Zenius Education is a technology-based education company from Indonesia. Zenius provides education access services in Indonesian language video formats which are presented online through the website (zenius.com) and mobile phone applications. On the Zenius web there are many features and tutors that can make learning easier. The usability of the website according to Nielsen, namely learnbility, efficiency, memorability, errors, and satisfactions, the usability contained on the Zenius website is able to attract users because it is easy to use the Zenius website. This journal will discuss the analysis of the quality and usability of the Zenius website based on the views of various people who have used the Zenius website, so that it can make it easier for companies to improve the website so that Zenius website users are satisfied.